Characteristics of banana fruits (Musa spp. AAA, cv. Nanica) treated with cytokinin and gibberellin - Lima, Juliana D. [UNESP]; Santa Rosa, Jessica [UNESP]; Gomes, Eduardo N. [UNESP]; Rozane, Danilo E. [UNESP]; Modenese-Gorla da Silva, Silvia H. [UNESP] (Pontificia Univ Catolica Chile, Fac Agronomia Ingenieria Forestal, 2016)
The aim of this study was to analyze the effect of cytokinin and gibberellin on the characteristics of banana fruits (Musa spp. AAA, cv. Nanica) as a function of the formation period and position in the bunch. A completely randomized, 2x5 factorial design was adopted consisting of two bunch development periods (summer and winter) and five treatments as well as the same arrangement in a split plot with the 2x5 factorial arrangement as the plot and the position of the hand in the bunch (basal, middle and apical) as the subplot. Treatments consisted of spraying twice with either water, 150 mg L-1 of kinetin, 200 mg L-1 of gibberellic acid, 100 mg L-1 of kinetin plus 200 mg L-1 of gibberellic acid or 200 mgL(-1) of kinetin plus 200 mg L-1 of gibberellic acid, all of which were applied from the fourth to the last hand of the bunch. The bunch formation period influenced the filling time, the mass of the bunch and the stalk, the number and the mass of the hands, the number of fruits per hand, fruit size, and the position of the fruit in the bunch as well as the time postharvest shelf life, mass loss, peel color, pH, the soluble solids content and the titratable acidity of the pulp. As applied, the cytokinin and gibberellin did not influence the yield or fruit size, but bunch position had a strong influence on the size and number of fruits per hand.
Keywords: Growth regulators; intra-bunch variability; source-sink relationship